(untitled) ("Conference on Universal Science Research 2023", 2025)
This article explores the integration of modern technologies in teaching foreign languages to young learners, focusing on the benefits, challenges, and effectiveness of various digital tools in language acquisition. It reviews existing literature on the impact of technologies such as mobile apps, interactive software, online platforms, and multimedia resources in enhancing motivation, engagement, and language retention. The study highlights how these tools facilitate personalized learning, offer real-time feedback, and support diverse learning styles. However, it also addresses concerns about over-reliance on technology and the need for a balanced approach that combines traditional teaching methods with digital innovations. The article provides valuable insights for educators and researchers seeking to understand the evolving role of technology in foreign language education for young learners